Correction to: Nobel somatosensations and pain (Pflügers Archiv - European Journal of Physiology, (2022), 474, 4, (405-420), 10.1007/s00424-022-02667-x) - Reeh, Peter; Fischer, Michael J. M. (Pflügers Archiv: European Journal of Physiology, 2022)
The online version of the article contains an error. Reference #2 should be replaced by: Adriaensen H, Gybels J, Handwerker HO, Van Hees J (1984) Nociceptor discharges and sensations due to prolonged noxious mechanical stimulation—a paradox. Human Neurobiol 3: 53–58. The original article has been corrected.
CRIS-Team Scopus Importer:2022-04-15